Adangiyah Konsep Gendhing-Gendhing Tradisi Gaya Surakarta - Suraji Suraji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2008)
In the Javanesse karawitan ~ society, the term of adangiyah, more perceivable as a lagu ‘s sentence of rebab and bonang barung, it ‘s performed before buka and after adalaras (rebab) or grambyangan (bonang barung) in partly pelog’s gendhings. This comprehension related with the definition ofadangiyahfrom Bau Sastra Jawa and used in the writing ofaksara Jawa have the similar meaning, because the adangiyah in the Javanesse gendhings always posted in the beginning before a buka gendhing.Keyword : adangiyah, buka, angsara jawa